The Sources and Effects of Risks of Forms of Islamic Financing in the Islamic Branches of the Commercial Bank - التميمي عباس حميد; حمادي ثورة صادق (Journal of Economics and Administrative Sciences, 2014)
Proved Islamic banks in many countries where they are present, whether Muslim or non-Muslim in the wake of the global financial crisis, it is more efficient, profitable, and stable compared with the conventional banks, so went many of the worlds towards providing Islamic banking through Islamic windows to Besides financial services and products offered by the traditional, or the initiative to enter formulas Islamic finance is fully compliant with the principles and rules of Islamic law and is Brokerage basic function of conventional banks and Islamic alike ) and that means working on the mobilization of savings from surplus units and directed towards the financial units of the fiscal deficit) , which operates commercial banks To receive deposits from the first category and then lending to the economic units and the relevant authorities fiscal deficit versus fixed income (interest), and this Matahramh Islamic law (where that money begets money. The Islamic Bank shall work on the receipt of funds from savers to The basis of formulas Islamic finance (through Murabaha and participation, etc.), and then work to employ them in the types of transactions allowed religiously, which are the posts or the sales of the other, and through cooperation between the capital and the organization under the Islamic economy is based on the principle of participation in the profit and loss and who can Altobeiranh to bear the risk. Therefore, researchers in Islamic banking often Estdlon rules doctrinal famous rule " abscess security " base " profits and losses sharing " and also some conversations Knhia God bless him and for-profit as evidence that the profit is not permissible except to assume the risk